PEMBERDAYAAN MASYARAKAT HUKUM ADAT (MASYARAKAT DESA) DALAM MENDUKUNG PROGRAM EKONOMI KREATIF DESA SESUAI UU DESA - Aartje Tehupeiory (to-ra, 2019)
Abstract For the empowerment of village communities in supporting the Village Creative Economy Program, which is to nd creative and innovative thinking models to build villages in an innovative model of empowering communi-ties in poverty reduction given to rural communities through educational innovations, innovations in the utiliza-tion of vacant land, traditional market management innovations, innovation village based or village. a quality community was formed in the rural areas to provide digital education for business development and community empowerment to help community businesses and micro and small businesses. Keywords: village community empowerment, village creative economy